Generalized Anxiety Disorder: Epidemiology, Prognosis, Non-Pharmacologic Treatment - ÜNSALVER, Barış Önen; BALCIOĞLU, İbrahim (Cerrahpaşa Medical Journal, 2014)
Generalized Anxiety Disorder(GAD), is a common anxiety disorder and an important public health issue. GAD has high psychiatric comorbidity, especially with major depression, panic disorder and substance abuse. However, because of the nature of the disease, these patients frequently present with somatic complaints to primary care physicians or to other general medicine physicians rather than the psychiatrists. When recognized and referred to psychiatry, these patients may have the chance of receiving appropriate treatment. GAD, has a lifetime waxing and waning course, therefore, introduction of specific psychotherapeutic techniques and development of coping skills in addition to pharmacologic interventions may promise a better prognosis.